Hedging in the Discussion Section of Research Articles Written by Native and Non-Native Writers of English - Tan, Helen (2002)
Hedging as a pragmatic-discourse phenomenon has gained much attention among academics and linguists researching the English language as well as other languages. The use of hedging is a significant communicative resource for academic writers to put forth their claims without the fear of being negated by the discourse community. This study compared the use of hedges in the discussion section of Research Articles (RAs) of two groups of writers (native versus Malaysian) and of two different disciplines (humanities versus science). For this purpose, the hedging patterns in 40 RAs (10 each from the two groups of writers and the two different disciplines) were analysed contextually. The findings from the study showed that both the native writers and Malaysian writers generally did use hedges in the discussion section of their RAs. However, by comparison, the native writers tended to hedge more than Malaysian writers. In addition, it was also found that formulaic hedging expressions were popular among Malaysian writers. In comparing between the disciplines, writers of the science discipline appeared to hedge slightly more than writers from the humanities disciplines. In sum, hedging is an important rhetorical device that permeates academic writing and therefore, language instructors should sensitize their writing students to the effective use of hedging in academic writing.